2022
DOI: 10.3389/fmicb.2022.971426
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effect of wilting on fermentation profiles and microbial community structure during ensiling and air exposure of king grass silage

Abstract: In order to better understand the effect of wilting treatment on silage, we study analyzed the fermentation quality of unwilted (CK) and wilted (WT) king grass silage, and the dynamic changes of microorganisms in silage and aerobic exposure. After 30 days of silage, WT silage significantly reduced the pH of the silage (p < 0.05) and increased the contents of lactic acid and acetic acid (p < 0.05), but did not reduce the content of Ammonia-N (p > 0.05). Wilting treatment increased bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
2
4
0
Order By: Relevance
“…The Saccharomyces belonging to lactate-assimilating yeasts have been proven to be associated with aerobic spoilage during aerobic exposure [61], which could utilize lactic acid, resulting in an increase in silage temperature and pH [55]. In the present trial, Saccharomyces was the most differentially abundant fungal in the HO treatment during the entire aerobic exposure period, suggesting that the yeast was the most important group of microorganisms causing silage deterioration upon aerobic exposure, which in agreement with the study published by Chen et al [15], who reported that the presence of yeast could induce the increase in pH value, thereby promoting the proliferation of the spoilage microorganisms. This finding may be attributed to the oat could be easily colonized by mycotoxigenic fungi [50].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The Saccharomyces belonging to lactate-assimilating yeasts have been proven to be associated with aerobic spoilage during aerobic exposure [61], which could utilize lactic acid, resulting in an increase in silage temperature and pH [55]. In the present trial, Saccharomyces was the most differentially abundant fungal in the HO treatment during the entire aerobic exposure period, suggesting that the yeast was the most important group of microorganisms causing silage deterioration upon aerobic exposure, which in agreement with the study published by Chen et al [15], who reported that the presence of yeast could induce the increase in pH value, thereby promoting the proliferation of the spoilage microorganisms. This finding may be attributed to the oat could be easily colonized by mycotoxigenic fungi [50].…”
Section: Discussionsupporting
confidence: 91%
“…In general, there are many factors affecting aerobic stability, such as undissociated acetic acid in plants and the development of yeasts and molds. However, recent research has demonstrated that the improvement of aerobic stability in silage is closely related to dynamic changes in microorganisms during the aerobic exposure stage [15]. The composition and distribution of fugal are the key players in aerobic stability.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there have many reports on the bacterial community changes during the ensilage process (Bai et al., 2022 ; Muraro et al., 2021 ; Ogunade et al., 2018 ), however, fungal community also had great impact on silage fermentation quality. Generally, Penicillium and Aspergillus are considered toxin producers, which affect the feeding safety of silages (Chen et al., 2022 ). Similar to the bacterial community, fungal community were also affected by the inoculation mentioned in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, considering the presence of Acinetobacter in the mixed silage and the increase in acetic acid levels with the prolongation of ensiling time, it is speculated that some Acinetobacter utilize acetic acid to survive in the anaerobic stage of silage. Chen et al also detected Acinetobacter in the king grass silage [ 45 ]. Klebsiella , a facultative anaerobic bacterium, has been found in many silages [ 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%